Altered mitochondrial genome content signals worse pathology and prognosis in prostate cancer. Issue 1 (14th November 2017) - Kalsbeek, Anton M. F.; Chan, Eva K. F.; Grogan, Judith; Petersen, Desiree C.; Jaratlerdsiri, Weerachai; Gupta, Ruta; Lyons, Ruth J.; Haynes, Anne‐Maree; Horvath, Lisa G.; Kench, James G.; Stricker, Phillip D.; Hayes, Vanessa M.
Abstract : Background: Mitochondrial genome (mtDNA) content is depleted in many cancers. In prostate cancer, there is intra‐glandular as well as inter‐patient mtDNA copy number variation. In this study, we determine if mtDNA content can be used as a predictor for prostate cancer staging and outcomes. Methods: Fresh prostate cancer biopsies from 115 patients were obtained at time of surgery. All cores underwent pathological review, followed by isolation of cancer and normal tissue. DNA was extracted and qPCR performed to quantify the total amount of mtDNA as a ratio to genomic DNA. Differences in mtDNA content were compared for prostate cancer pathology features and disease outcomes. Results: We showed a significantly reduced mtDNA content in prostate cancer compared with normal adjacent prostate tissue (mean difference 1.73‐fold, P ‐value <0.001). Prostate cancer with increased mtDNA content showed unfavorable pathologic characteristics including, higher disease stage (PT2 vs PT3 P ‐value = 0.018), extracapsular extension ( P ‐value = 0.02) and a trend toward an increased Gleason score ( P ‐value = 0.064). No significant association was observed between changes in mtDNA content and biochemical recurrence (median follow up of 107 months). Conclusions: Contrary to other cancer types, prostate cancer tissue shows no universally depleted mtDNA content. Rather, the change in mtDNA content is highly variable, mirroring known prostate cancer genome heterogeneity. Patients with high mtDNA content have an unfavorable pathology, while a high mtDNA content in normal adjacent prostate tissue is associated with worse prognosis.